Lost in translation? ECB's monetary impulses and financial intermediaries' responses - Günter Wilfried Beck; Hans-Helmut Kotz; Natalia Zabelina (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
Non-bank (-balance sheet) based financial intermediation has become considerably more important over the last couple of decades. For the U.S., this trend has been discussed ever since the mid-1990s. As a consequence, traditional monetary transmission mechanisms, mainly operating through bank balance sheets, have apparently become less relevant. This in particular applies to the bank lending channel. Concurrently, recent theoretical and empirical work uncovered a "risk-taking channel" of monetary policy. This mechanism is not confined to traditional banks but has been found to operate also across the spectrum of financial intermediaries and intermediation devices, including securitization and collateralized lending/borrowing. In addition, recent empirical evidence suggests that the increasing importance of shadow-banking activities might have given rise to a so-called "waterbed effect". This is a mediating mechanisms, dampening or counteracting typically to be expected reactions to monetary policy impulses. Employing flow-of-funds data, we can document also for the Euro Area that a trend towards non-bank (not necessarily more 'market'-based) intermediation has occurred. This is, however, a fairly recent development, substantially weaker than in the U.S. Nonetheless, analyzing the response of Euro Area bank and nonbank financial intermediaries to monetary policy impulses, we find some notable behavioral differences between mainly deposit-funded and more 'market'-based financial intermediaries. We also detect, inter alia, the existence of a (still) fairly weak, but potentially policyrelevant, "waterbed" effect.
urn:nbn:de:hebis:30:3-400607
Keywords: 330; non-bank financial intermediation; interest-rate channel; credit channel; risk-taking channel of monetary policy; market-based financial intermediation; monetary transmission mechanism; waterbed effect